2D MoS2/carbon/polylactic acid filament for 3D printing: Photo and electrochemical energy conversion and storage. (March 2022) - Ghosh, Kalyan; Ng, Siowwoon; Iffelsberger, Christian; Pumera, Martin
Highlights: A (photo)electrocatalytic active MoS2 /C/PLA filament was fabricated for FDM printing. The MoS2 /C 3D electrode showed high photocatalytic activity in the red wavelength region. The free-standing MoS2 /C 3D electrode showed high areal capacitance and cyclic stability. Abstract: Fused deposition modeling (FDM) 3D printing has attracted immense attention in the field of energy conversions and storage for rapid prototyping and fabrication of devices in a facile and customized way. In this study, we fabricated an electrocatalytically active filament for FDM printing comprised of catalytically active material, conductive fillers, and polymer. We explored the different mass loading of conductive fillers (graphite, activated charcoal and multi-walled carbon nanotubes) with respect to the base polymer polylactic acid (PLA) to optimize a filament with good flexibility and conductivity. To obtain the (photo)electrocatalytically active filament, an active material was added into the optimized carbon/polymer filament to fabricate the 3D-printed electrodes. We selected MoS2 as an archetypal 2D material to demonstrate the functionality of the 3D electrodes in energy conversion and storage applications by the bespoke filament. The 3D-printed MoS2 /carbon electrode shows good (photo)electrocatalytic hydrogen evolution reaction and high capacitive performance. The optimized filament fabrication protocols mitigate the complex fabrication of electrodes by fine-tuning the ratio of polymers and conductive fillers to desired active material such as other 2D materials. This allows the production of many other tunable 3D-printed electrodes for energy conversion and storage and other electrochemical applications. Abstract : Image, graphical abstract